Risky driving behaviours of car and motorcyclist crashes in relation to road accidents among malaysians - Shahrin Nabil, Mohamad Norman (2025)
Road accidents remain a critical issue in Malaysia, with a particularly high incidence involving cars and motorcyclists. This study aims to examine the relationship between risky driving behaviours and the severity of both commuting and general road accidents among Malaysian drivers and riders. A cross-sectional quantitative approach was adopted using a validated questionnaire distributed to individuals involved in accidents between 2016 and 2025. The data, analyzed using SPSS software, revealed that fatigue, speeding, and distractions were the most prevalent risky behaviours. A moderate positive correlation was found between risky behaviours and accident severity in both contexts; however, commuting accidents often involved longer travel distances and occurred more frequently in poor weather conditions compared to non-commuting accidents. These findings underscore the need for differentiated preventive strategies addressing both general road use and daily commuting, such as targeted safety programs, awareness campaigns, and improvements in road infrastructure.